Improvement of Response Time Using a New Identity Management Framework in Internet of Things - جولحة الفت; ابراهيم عبير (Latakia University Journal -Engineering Sciences Series, 2021)
The Internet of Things )IoT( is an advanced concept of the traditional Internet so that objects have internet connectivity or each other to send and receive data to perform specific functions through the network. Identity Management (IdM) provides authentication and internet access authorization, so it is important to use it with Internet of Things (IoT). This research suggests designing a new identity management (IdM) framework in Internet of Things (IoT) taking into account both the realization of a secure communication channel and the fact that IoT devices are only devices with limited resources, forcing mechanisms to reduce the consumption of these resources. The performance of the proposed framework is verified by conducting scenarios using Cooja, according to a set of performance-impact parameters. The proposed identification framework provides an improvement in response time.